Degradação térmica em filmes de polietileno reticulados - Barros, Ana Beatriz de Sousa (2021)
The study of the packaging's mechanical properties makes it possible to create an alternative in the process of extending the product's useful life, since a certain product to be filled deteriorates more easily than another, under the same conditions. You can develop combinations of materials with different properties that suit each case, avoiding over-packaging and ensuring food protection. PE films are the most used for flexible packaging production, representing 32% of the total market share. Crosslinking PE is of considerable practical importance, extends the range of use by increasing the upper application temperature limit and improves its mechanical properties. In this context, this study aims at morphological change for the production of flexible packaging aiming at better thermal degradation. Compositions with 0%, 0.5%, 1.0% and 1.5% of the crosslinking agent (Retilox) were investigated in an industrial batch, to produce thermoplastic systems with cross-links between the polymer chains. The films were characterized by Fourier Transform Infrared Spectrometry (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), mechanical properties and a study of degradation kinetics using Friedman and ASTM E698 models for Ozawa. The FTIR analysis of the films showed that the band at 870 cm-1 increased in intensity with increasing concentration of Retilox, suggesting a greater interaction of the aromatic ring present in the Retilox structure with polyethylene (PE). From the DSC it was observed that the crystallization rate increased with cooling rates and decreased with the addition of Retilox, while the degree of crystallinity was subtly affected during melting, the crystallization from crosslinked PEs exhibited degree of higher crystallinity. TGAs showed that increasing heating rates, dα/dt is shifted and mass loss temperatures are observed at higher temperatures, indicating greater thermal stability, and retilox increased and shifted the graphs to higher temperatures, suggesting that the retilox contributes to PE stabilization. The mechanical properties showed that the crosslinked PEs had higher modulus of elasticity and lower deformation at break. For the two models used to study the degradation kinetics, similar behaviors of the samples were observed, where Ea increased with the course of degradation and morphological and structural changes caused by crosslinking are observed in larger Ea. There are also significant variations in the 1.5XPE composition, where negative Ea values are observed, indicating that low energy reactants react faster than high energy ones, the more stable the molecule, the lower its energy. Thus, the best composition would be 0.5XPE where they presented greater thermal stability, better mechanical properties, and regardless of the atmospheres studied, they presented acceptable values in both kinetic studies performed, showing acceptable discrepancy and good performance in all data.